2018
DOI: 10.3390/jof4020065
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activities of Volatile Secondary Metabolites of Four Diaporthe Strains Isolated from Catharanthus roseus

Abstract: Four endophytic fungi were isolated from the medicinal plant, Catharanthus roseus, and were identified as Diaporthe spp. with partial translation elongation factor 1-alpha (TEF1), beta-tubulin (TUB), histone H3 (HIS), calmodulin (CAL) genes, and rDNA internal transcribed spacer (ITS) region (TEF1-TUB-HIS--CAL-ITS) multigene phylogeny suggested for species delimitation in the Diaporthe genus. Each fungus produces a unique mixture of volatile organic compounds (VOCs) with an abundant mixture of terpenoids analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 49 publications
2
17
0
Order By: Relevance
“…This investigation showed that VOCs produced by the endophytic D apiculatum FPYF 3052 were able to inhibit the growth of fungal pathogens (Table 2). This result was consistent with evidence on the VOCs of some endophytic fungi of Diaporthe previously reported [7,14,15,17]. These fungi were recorded as Diaporthe sp.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This investigation showed that VOCs produced by the endophytic D apiculatum FPYF 3052 were able to inhibit the growth of fungal pathogens (Table 2). This result was consistent with evidence on the VOCs of some endophytic fungi of Diaporthe previously reported [7,14,15,17]. These fungi were recorded as Diaporthe sp.…”
Section: Discussionsupporting
confidence: 92%
“…The roots and leaf extracts of L. leucocephala have also demonstrated antimicrobial and antifungal activities [5]. At present, there is some evidence to show that endophytes could have a potential function in inhibiting harmful pests, like Aspergillus fumigatus, Botrytis cinerea, and Mycobacterium tuberculosis [6][7][8]. However, more endophytes of L. leucocephala need to be isolated and studied for their diversity and function in disease protection since only the ones studied so far are linked to nitrogen fixation, mycorrhizal associations, along with some seed-associated fungi [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations